2020
DOI: 10.1136/bmj.m1714
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the credibility of anchor based estimates of minimal important differences for patient reported outcomes: instrument development and reliability study

Abstract: Objective To develop an instrument to evaluate the credibility of anchor based minimal important differences (MIDs) for outcome measures reported by patients, and to assess the reliability of the instrument. Design Instrument development and reliability study. Data sources Initial criteria were developed for evaluating the credibility of anchor based MIDs based on a literature review (Medline, Embase, CINAHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
220
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(228 citation statements)
references
References 90 publications
(131 reference statements)
5
220
1
2
Order By: Relevance
“…Given the relatively long interval between the baseline and first follow-up, risk of recall bias is obvious. This notion is supported by very low correlations between the transition item and baseline and lower correlations to change scores than to the post scores [ 21 , 22 ]. This is an inherent weakness of the GRC in a setting where the condition needs longer to evolve than a reliable recall time frame [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the relatively long interval between the baseline and first follow-up, risk of recall bias is obvious. This notion is supported by very low correlations between the transition item and baseline and lower correlations to change scores than to the post scores [ 21 , 22 ]. This is an inherent weakness of the GRC in a setting where the condition needs longer to evolve than a reliable recall time frame [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…An adequate transition anchor should correlate to the change in outcome, and ideally correlate equally, but in opposite directions to the scores of outcomes at baseline and at follow-up time points (post scores) [ 21 ]. The correlation to change should be larger than the correlation to post scores when the GRC captures true change [ 22 ]. To explore this, we calculated the correlation coefficients (Spearman’s rho) for the GRC answers at different time points and baseline scores, the GRC and each of the respective post scores and the post scores of the combined dataset, and the GRC and the change scores of the outcomes, also at follow-up time points and the combined dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Before statistical analyses, we calculated the minimal important change (MIC) of the PSFS in our population, using an anchor-based method, to provide a context of clinical relevance. 7 The anchor question was the following: “How did your function in daily activities change since the surgery/treatment of your knee?” A detailed description of the methods and results for the MIC calculation can be found in Appendix 2.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies the values of MCID were reported as 1.0 (VAS), 26 5.5(CMS), 14.88 (SPADI), and 11.1 (ASES), 27, 28 respectively. In this study, the minimal important differences (MIDs) between two groups calculated by anchor-based methods 29 were compared with those MCIDs. Therefore, clinical improvements were deemed meaningful when the MIDs calculated were beyond MCIDs.…”
Section: Methodsmentioning
confidence: 99%